2018
DOI: 10.3389/fmicb.2018.01974
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Classification for the Lactobacillus casei Group

Abstract: Lactobacillus casei, Lactobacillus paracasei, and Lactobacillus rhamnosus are phenotypically and genotypically closely related, and together comprise the L. casei group. Although the strains of this group are commercially valuable as probiotics, the taxonomic status and nomenclature of the L. casei group have long been contentious because of the difficulties in identifying these three species by using the most frequently used genotypic methodology of 16S rRNA gene sequencing. Long used as the gold standard for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 125 publications
(157 reference statements)
1
45
0
4
Order By: Relevance
“…[8] Thefunction of xoxF had been long unknown, in fact the first "x" in xoxF stands for its (previously long) unknown role. [9] In the same year,t he authors also reported ac erium(III)-dependent MDH in Bradyrhizobium sp.M AFF211645. [10] One year later, Nakagawa and Kawai reported that the model methylotroph strain M. extorquens AM1 also produced al anthanide-dependent MDH and that this bacterium could grow with La 3+ instead of Ca 2+ .…”
Section: Discovery Of Lanthanide-dependent Proteinsmentioning
confidence: 91%
See 1 more Smart Citation
“…[8] Thefunction of xoxF had been long unknown, in fact the first "x" in xoxF stands for its (previously long) unknown role. [9] In the same year,t he authors also reported ac erium(III)-dependent MDH in Bradyrhizobium sp.M AFF211645. [10] One year later, Nakagawa and Kawai reported that the model methylotroph strain M. extorquens AM1 also produced al anthanide-dependent MDH and that this bacterium could grow with La 3+ instead of Ca 2+ .…”
Section: Discovery Of Lanthanide-dependent Proteinsmentioning
confidence: 91%
“…[2e, 22] While the affinity of Ln of LanM in in vitro experiments is very similar for all lanthanides, [20] the choice of Ln has been shown to affect the growth rate of bacteria and also the activity of alcohol dehydrogenases. [9,23] Mainly,t he earlier lanthanides (La to Sm) are known to stimulate the growth of Ln-utilizing bacteria (Figure 3). It is possible that efficient 18] In the presence of lanthanides,XoxF (Ln-MDH, golden pathway)i se xpressed and MxaF (Ca-MDH, grey pathway)i srepressed.…”
Section: Importance Of Lanthanides In Microbiologymentioning
confidence: 99%
“…The amplification and sequencing of the 16S rRNA gene and housekeeping genes (dnaJ, dnaK, mutL, pheS and yycH) were carried out as previously described [19][20][21][22][23]. Multiple sequence alignments were performed with the program clustal_x version 2.1 [24].…”
mentioning
confidence: 99%
“…[2e,21] Während die Ln-Affinitätv on LanM bei In-vitro-Experimenten füra lle Lanthanoide ähnlich ist, [19] konnte gezeigt werden, dass die Wahl von Ln das Wachstum von Bakterien und die Aktivitätv on Alkohol-Dehydrogenasen beeinflusst. [9,22] [23] Des Weiteren haben Wachstumsstudien mit M. fumariolicum SolV gezeigt, dass La 3+ schneller aus dem Medium abgereichert wird als Eu 3+ -e ine Beobachtung,d ie mit der Wachstumsgeschwindigkeit korreliert. [26] Abbildung 3z eigt, dass besonders die früheren, häufiger vorkommenden Lanthanoide das Wachstum von Bakterien, die Ln-abhängige Enzyme exprimieren, unterstützen.…”
Section: Angewandte Chemieunclassified
“…[8] Die Funktion von xoxF war lange unbekannt, das erste "x" in xoxF steht tatsächlich fürdiese lange unbekannte Rolle. [9] Im selben Jahr noch berichteten die Autoren über eine Cer(III)abhängige MDH in Bradyrhizobium sp.MAFF211645. [10] Ein Jahr später konnten Nakagawa, Kawai et al berichten, dass der Modell-Bakterienstamm Methylorubrum extorquens AM1 ebenfalls eine Lanthanoid-abhängige MDH exprimiert und dass diese Bakterien mit La 3+ anstatt von Ca 2+ wachsen kçnnen.…”
Section: Introductionunclassified